A new Erichsonius species from Taiwan (Coleoptera: Staphylinidae, Staphylininae): descriptions of adult and larva associated by DNA barcodes, and a checklist of Oriental and East Palaearctic species of the genus - Uhlig, Manfred; Uhlig, Barbara; Hu, Fang-Shuo; Fikáček, Martin (Zootaxa, 2026)
Erichsonius (Sectophilonthus) huisunensis sp. nov. from Taiwan is described and photo-documented in detail, based on adult males, females, and larvae. It differs from other known Erichsonius species by its unusually brightly coloured elytra, but shows affinity to the Oriental group of winged, sparsely punctate smaller species with abdominal segments IV–V widest and with larger eyes. The species is common and widespread in the Central Mountain Range in Taiwan at altitudes 400–1800 m, where it inhabits forest floor and leaf litter. DNA barcodes are provided for the holotype and several paratypes. The late-instar larvae of the new species, associated with adults by DNA barcodes are also described and illustrated. A checklist of Erichsonius species occurring in the Oriental and East-Palaearctic regions, along with their type locality and distribution data, is also provided.